Synthesis and Characterization of Oxovanadium(IV) Urea Compound - A. Hassan, Kh.; Al-Hashimi, N.A.; Nour, E.M. (Asian Journal of Chemistry, 2016)
Vanadyl chloride, VOCl2·6H2O, reacts with urea at room temperature to form the four coordinated oxovanadium(IV) complex of the type [V(O)(urea)2(Cl)2]. The complex is in the mononuclear form where the two urea molecules and two chlorides occupy the four equatorial positions in a plane perpendicular to the vanadyl oxygen forming a distorted square pyramid.